Cycloaddition reactions of glycine imine anions to phenylazocarboxylic esters - A new access to 1,3,5-trisubstituted 1,2,4-triazoles - Lasch, Roman; Heinrich, Markus (Tetrahedron, 2015)
Phenylazocarboxylic tert-butyl esters have recently been shown to be highly versatile building blocks due to their ability to undergo nucleophilic aromatic substitutions under mild conditions, particularly well with [18F]fluoride, and to act as precursors for aryl radicals. In this article, we now report first examples for cycloaddition reactions to phenylazocarboxylates. In a one-pot reaction with readily accessible glycine imines, a variety of highly substituted 1,2,4-triazoles could be obtained.
Keywords: 1; 2; 4-Triazoles; Azo compounds; Azocarboxylic esters; Cycloaddition; Glycine imines